The eden test eaudiobook A novel. - Sternbergh, Adam (Macmillan Audio, 2023)
"Narrator Carlotta Brentan performs fascinating monologues of Daisy and Craig. She captures the rhythm and the cadence of each of their voices and does a fine job of revealing their distinct personalities. As the story unfolds and Daisy and Craig find themselves in physical danger, Brentan's ability to ramp up the tension to an excruciating level will have listeners squirming in their earbuds." - AudioFile Magazine "A galloping and exhilarating thriller." —Laura Dave, New York Times bestselling author of The Last Thing He Told Me From Edgar Award-finalist Adam Sternbergh, an electrifying domestic suspense novel for fans of The Perfect Marriage and Rock Paper Scissors , about a couple who are forced to the ultimate extremes to save their marriage—and themselves. Seven Days. Seven Questions. Forever Changed. Daisy and Craig's marriage is in serious trouble. That's why Daisy has signed up for The Eden Test, a week-long getaway for couples in need of a fresh start. Yet even as she's struggling to salvage her marriage, it seems Craig has plans to leave her for another woman. In fact, his bags are already packed—long before he arrives to meet Daisy in this remote cabin in the woods of upstate New York. At first, their week away is marked by solitude, connection, and natural beauty—and only a few hostile locals. But what Craig doesn't know is that Daisy, a slyly talented actress, has her own secrets, including a burner phone she's been using for mysterious texts. Not to mention the Eden Test itself, which poses a searing new question to the couple every day, each more explosive than the last. Their marriage was never perfect, but now the lies and revelations are piling up, as the week becomes much more than they bargained for...How far are they willing to go? Adam Sternbergh brings his wit, originality, and a Hitchcockian sense of dread to this chilling, surprising, and wholly entertaining portrait of a marriage on the brink. A Macmillan Audio production from Flatiron Books.